(untitled) (Universal International Scientific Journal, 2026)
This article describes the role of pedagogical responsibility in the educational process as one of the important professional characteristics and its main aspects in the activities of a future teacher. Also, suggestions and recommendations are put forward on the methods of forming and developing pedagogical responsibility in preparing future teachers for professional activity in higher educational institutions, as well as their use in the didactic process.